Fabrication and drug release properties of curcumin-loaded silk fibroin nanofibrous membranes. Issue 5 (July 2019) - Xie, Xusheng; Yu, Jia; Zhao, Zeyu; Zheng, Zhaozhu; Xie, Maobin; Wang, Xiaoqin; Han, Zhifen; Li, Gang
This paper describes a silk fibroin-based nanofibrous membranes loaded with antitumor drugs curcumin and 5-fluorouracil using electrospinning technique. The concentration of curcumin/5-fluorouracil in the silk fibroin solution for electrospinning was optimized to be 0.15/0.25, 0.3/0.5, and 0.45/0.75 wt%. The morphology, hydrophilic property, pore size, secondary structure, and antitumor drugs release of nanofibrous membranes were measured. The diameter of nanofibrous membranes ranged about 100–200 nm. The results indicated that electrospinning process did not influence the secondary structure and the drug content of antitumor drugs, and dual drugs encapsulated in the silk fibroin nanofibrous membranes were released in a steady and consistent process. In conclusion, the silk fibroin-based drug-loaded membranes can be useful as biomaterials with antitumor function.